2005
DOI: 10.1140/epjd/e2005-00088-6
|View full text |Cite
|
Sign up to set email alerts
|

Cold atoms in videotape micro-traps

Abstract: We describe an array of microscopic atom traps formed by a pattern of magnetisation on a piece of videotape. We describe the way in which cold atoms are loaded into one of these micro-traps and how the trapped atom cloud is used to explore the properties of the trap. Evaporative cooling in the micro-trap down to a temperature of 1 µK allows us to probe the smoothness of the trapping potential and reveals some inhomogeneity produced by the magnetic film. We discuss future prospects for atom chips based on micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…This introduces a spatially varying magnetic field component parallel to the wire which corrugates the bottom of the trap potential. While more advanced microfabrication techniques have been used to produce wires with extremely straight edges, thereby minimizing fragmentation [18,19], the first experiments with permanent magnet atom chips have now also indicated the presence of significant fragmentation [12,20,21]. This has motivated further work towards understanding the mechanisms that cause fragmentation near magnetic materials.…”
mentioning
confidence: 99%
“…This introduces a spatially varying magnetic field component parallel to the wire which corrugates the bottom of the trap potential. While more advanced microfabrication techniques have been used to produce wires with extremely straight edges, thereby minimizing fragmentation [18,19], the first experiments with permanent magnet atom chips have now also indicated the presence of significant fragmentation [12,20,21]. This has motivated further work towards understanding the mechanisms that cause fragmentation near magnetic materials.…”
mentioning
confidence: 99%
“…It has been shown that Bose-Einstein condensation can be achieved on atom chips, both with current-carrying wire traps 15 and with permanent magnet traps. 16 Consequently it may be possible to create an array of condensates loaded from these MOTs. Alternatively, if there is just one atom per site, the array would have possible applications in quantum information processing.…”
mentioning
confidence: 99%
“…17,18 If a FG film is designed to have large coercivity and high saturation magnetization, magneticdomain patterns recorded on the film can be used as miniature optically transparent permanent magnets, e.g., in the manipulation of magnetic colloidal particles [19][20][21] and trapping of dilute gaseous samples of laser-cooled atoms. [22][23][24] In the past few years, research attention has also been paid to ultrafast magnetization phenomena in FG materials. By employing a FG film that has in-plane magnetization and essentially no domain activity, all-optical modulation of the direction of magnetization on the femtosecond time scale has been demonstrated.…”
Section: -4mentioning
confidence: 99%